SURGICAL MANAGEMENT OF OMPHALOMESENTERIC DUCT REMNANTS IN CHILDREN - Maroof, Syed Asad; Khan, Muhammad Jehangir; Khan, Yunus; Uzair, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To study the clinical presentation and surgical management of omphalomesenteric duct (OMD) remnants. Material and Methods: This was a prospective, descriptive study conducted at Pediatric surgery unit of Lady Reading Hospital, Peshawar from 1st January 2005 to 31st January 2008.Children below 15 years of age with operative diagnosis of omphalomesenteric duct (OMD) remnants were included in the study. Data was collected on a pre-designed standard proforma and patients were divided into three groups on the basis of operative procedure used to deal with OMD remnants. Group I included the patients in whom 'Wedge resection' of OMD remnants was performed. Group II included patients with 'Segmental ileal resection and end to end anastomosis' and Group III included patients having 'Ileostomy'. All the cases were followed for 6 months after operation. Results: Mean age was 4.23+3.53 years and Male: Female ratio was 2.6:1. Intestinal obstruction (44.7%) was the commonest presenting feature followed by diverticulitis (27.5%), intestinal perforation (10.3%), umblical discharge (10.3%) and duct prolapse (6.8%). Only one patient (3.4%) presented with haemorrhage. Overall mortality was 6.8% and hospital stay in cases of wedge resection was 9+2.179 days, in segmental ileal resection was 6.88+2.34 days and in Ileostomy was 4.67+0.57 days. Conclusion: Presentation of OMD remnants varies in different areas and the surgical protocols to deal with symptomatic cases of these malformations should be standardized through further studies.